Charles Dickens and His Pen Pals - Turner, Tracey; Goddard, Clive (New York : Scholastic, 2005)
You've probably heard of William Shakespeare and his popular plays; Jane Austen and her love stories; Charles Dickens and his big blockbusters. But have you heard that William Shakespeare got mixed up in a plot against the Queen? Jane Austen nearly became a Bigg-Wither? And Charles Dickens had his clothes ripped off by his fans?
Keywords: History and Leaders -- non-fiction